The Relationship between Peripheral Nerve Conduction Velocity and Ophthalmological Findings in Type 2 Diabetes Patients with Early Diabetic Retinopathy. (20th February 2018) - Ito, Azusa; Kunikata, Hiroshi; Yasuda, Masayuki; Sawada, Shojiro; Kondo, Keiichi; Satake, Chihiro; Hashimoto, Kazuki; Aizawa, Naoko; Katagiri, Hideki; Nakazawa, Toru
Abstract : Purpose. Nerve conduction velocity (NCV) is an indicator of neuronal damage in the distal segment of the peripheral nerves. Here, we determined the association between NCV and other systemic and ocular clinical findings, in type 2 diabetes patients with early diabetic retinopathy (DR). Methods. This study included 42 eyes of 42 type 2 diabetes patients (median age: 54 years) with no DR or with mild nonproliferative DR. Standard statistical techniques were used to determine associations between clinical findings. Results. Sural sensory conduction velocity (SCV) and tibial motor conduction velocity (MCV) were significantly lower in mild nonproliferative DR patients than patients with no DR (P = 0.008 andP = 0.01, resp.). Furthermore, logistic regression analyses revealed that sural SCV and tibial MCV were independent factors contributing to the presence of mild nonproliferative DR (OR 0.83, P = 0.012 and OR 0.69P = 0.02, resp.). Tibial MCV was correlated with choroidal thickness (CT) (P = 0.01 ), and a multiple regression analysis revealed that age, tibial MCV, and carotid intima-media thickness were independent associating factors with CT (P = 0.035, P = 0.015, andP = 0.008, resp.). Conclusions. Our findings suggest that reduced NCV may be closely associated with early DR in type 2 diabetes patients. Thus, reduced nerve conduction is a potential early biomarker of DR.